Ice Skating - Streeter, Michael, 1962- (Broomall, Pa. : Mason Crest Publishers, 2004)
Introduces the sport of ice skating and provides information on how to prevent and treat the most common ice skating injuries.
History -- Mental preparation to avoid injury -- Warming up to avoid injury -- Equipment -- Common injuries and treatment -- Careers in skating.
Includes bibliographical references (p. 62) and index.
Keywords: Skating -- Juvenile literature; Skaters -- Wounds and injuries -- Juvenile literature; Ice skating; Sports injuries